ROAMER: Roadside Units as message routers in VANETs - Mershad, Khaleel (2012)
Vehicular Ad hoc Networks, also known as VANETs, enable vehicles that are not necessarily within the same radio transmission range to communicate with each other. VANETs also allow vehicles to connect to Roadside Units (RSUs). The latter are connected to the Internet, forming a fixed infrastructure that offers them the capability of communicating with each other and with roaming vehicles. RSUs support cooperative and distributed applications in which vehicles and RSUs work together to coordinate actions and to share and process several types of information. RSUs have so far been used for different roles such as data disseminators, traffic directories, location servers, security managers, and service proxies. In this paper, we focus on routing; namely we exploit RSUs to route packets between any source and destination in the VANET. To our knowledge, this is the first attempt to use the RSU backbone to efficiently route packets to very far locations in VANETs by using geographic forwarding. We evaluate the RSU backbone routing performance via the ns2 simulation platform. We compare our scheme to existing solutions and prove the feasibility and efficiency of our scheme in terms of query delay, packet success delivery ratio, and total generated traffic.